Superelastic behavior of a metamagnetic Ni-Mn-Sn single crystal - Chulist, R.; Tokarski, T.; Czeppe, T.; Chumlyakov, Yuri I.; Cesari, Eduard; Czaja, P. (Journal of materials science)
A single-crystalline specimen with the composition of Ni49.5Mn38.4Sn12.2 shows a 4.9% recoverable transformation strain upon compressive loading. The critical compressive stress increases with temperature at the step of 5.6 MPa/K, whereas upon cycling it decreases by 18.1 MPa/cycle. The microstructure of the specimen undergoes considerable refinement upon superplastic training; however, it is only able to sustain a limited number of cycles (B 5). Martensite training, resulting in a single-variant microstructure, has a profound influence on the austenite start transformation temperature (DT = 29 K), resulting partially from the dissipation of the elastic strain energy. The Ni-Mn-Sn system is an interesting candidate for multiferroic applications given its mechano-magnetic properties and a huge value of the martensitic transformation entropy change (* 50 J/kg K).